The Role of Managerial and Professional Motivation in the Career Success of Management Professors - Miner, John B. (Academy of Management Journal, 1980)
Two limited domain theories of organizational motivation, the professional and the hierarchic, were tested in the professional context using professor members of the Academy of Management as subjects. As hypothesized, the results supported the professional theory, but not the hierarchic. Implications for professional practice and for professional organizations are considered.